Design ductile and work-hardenable composites with all brittle constituents. (15th April 2021) - Zhang, Yanming; Zhao, Huijuan; Deng, Binghui; Basu, Swastik; Huang, Liping; Shi, Yunfeng
Abstract: Metallic glasses, like many other glasses and ceramics, generally have zero tensile ductility. Distinct from common wisdom which seeks to toughen brittle glasses with ductile phases, we show that composites made from two brittle glasses can be ductile, strong and even harden under tension as a result of microstructure and stiffness contrast. Using molecular dynamics simulations, we designed and tested composites consisting of alternating wavy nanofilaments of two brittle glasses with different stiffness. The composites exhibit failure strain over 40% and strain hardening modulus over 2 GPa. The tensile ductility is determined by both the flexibility of nanofilaments and the propensity of crack deflection, with which a ductile composite design map can be constructed. The strain hardening is due to filament alignment analogous to linear polymer. The brittle-brittle composite design strategy proposed here is not material-specific and should be applicable to, for instance, ultra-hard materials as constituents in achieving new damage-resistance composites. Graphical abstract: Image, graphical abstract